2016
DOI: 10.1080/15321819.2016.1224973
|View full text |Cite
|
Sign up to set email alerts
|

Sialic acid level is significantly elevated in IgM enriched protein fraction in sera of cancer patients

Abstract: Serum sialic acid (SA) levels are important for diagnosis, follow-up, and mechanistic analysis of malignant diseases. However, little is known about the levels of SA bound to serum IgM. Here, we isolated IgM from sera of healthy individuals and patients with cancer using DEAE chromatography and 8% polyethylene glycol precipitation. In this fraction, which contained partially purified IgM (recovery; 52%; purity: 25%), SA was quantified with fluorescence detection-HPLC (detection limit: 0.08 μM). SA levels in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…In contrast, we observe signi cant differences in IgM Nglycosylation stratifying COVID-19 disease severity with decreases only in the processed M5 and M6 Nglycans. Another group reported higher levels of sialic acid detected in IgM protein fraction isolated from cancer patient sera compared to non-cancer patients [45] while another study reported no signi cant glycomic response associated with either IgG or IgM N-glycan pro les following tumor ablation therapy [44]. Our ndings expand upon the previous reports of a general increase in sialic acid content on IgM.…”
Section: Igm N-glycosylationsupporting
confidence: 79%
See 1 more Smart Citation
“…In contrast, we observe signi cant differences in IgM Nglycosylation stratifying COVID-19 disease severity with decreases only in the processed M5 and M6 Nglycans. Another group reported higher levels of sialic acid detected in IgM protein fraction isolated from cancer patient sera compared to non-cancer patients [45] while another study reported no signi cant glycomic response associated with either IgG or IgM N-glycan pro les following tumor ablation therapy [44]. Our ndings expand upon the previous reports of a general increase in sialic acid content on IgM.…”
Section: Igm N-glycosylationsupporting
confidence: 79%
“…While the N-glycosylation of IgM has been characterized previously in healthy pooled human serum, during cancer [35,[43][44][45], and in recombinant IgM [34,46], this is the rst characterization of the IgM Nglycosylation pro le isolated from humans infected with an acute viral disease. Here, we report signi cant differences in the IgM N-glycan content from cohorts of hospitalized COVID-19 separated by severity trajectory.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, sialic acid in a complex sample could easily be quantified by the HPLC and MS method, which could be applied in tumor research and diagnosis [26]. For example, sialic acid, quantified with fluorescence detection-HPLC in the IgM-enriched fraction, was significantly higher in cancer patients [112]. The sialylated proteins, as potentially cancer-associated proteins in serum, were quantified in prostate cancer using LC-MS/MS [113,114].…”
Section: Sialic Acids Quantificationmentioning
confidence: 99%
“…Considering the increased sialic acid content on total and spike S1-specific IgM from patients with severe COVID-19, one publication reported higher levels of sialic acid detected in IgM isolated from cancer patients 49 . During severe COVID-19, increased sialylation is likely presented on IgM glycosylation sites: Asn-395, Asn-332, and Asn-171 which could participate in immunomodulatory signaling.…”
Section: Discussionmentioning
confidence: 99%
“…While the N-glycosylation of IgM has been characterized previously in healthy pooled human serum, during cancer 38 , 47 49 , and in recombinant IgM 37 , 50 , this is the first characterization of the IgM N-glycosylation profile isolated from humans with an acute viral infection. Here, we report significant differences in the total and antigen-specific IgM N-glycan content from cohorts of hospitalized COVID-19 patients separated by severity, contrast these findings with patient’s IgG N-glycans, and identify potential functional consequences of IgM N-glycosylation.…”
Section: Introductionmentioning
confidence: 94%